A study on factors that influence the adoption of internet banking: a case of Kelantan banking customers / Nor Asyikin Abdul Aziz - Abdul Aziz, Nor Asyikin (2007)
Internet banking becomes the important modes of payment as world is moving towards a cashless society. It gives convenience and advantages to both financial institutions and banking customers. The provider of internet banking has increase and the awareness level is high but it is not translated into the actual usage of Internet banking. The previous research revealed that bank customers have different attitudes towards Internet banking. There is limited research conducted on Internet banking adoption by individual in Kelantan. This research intends to identify the level of adoption of internet banking and to recognize the factors that influence the adoption of Internet banking among banks account holders in Kelantan.